Intra and interspecific variation in foliage phenology and leaf spectroscopy in nine Baja Californian shrub species - Anaid Rodríguez Bastarrachea; Samantha D. Díaz de León; Stephen H. Bullock; Miguel Ángel Alonso Arévalo; Rodrigo Méndez-Alonzo (Botan‪ical Sciences, 2024)
Background: Canopy phenology, foliar biochemistry, and leaf lifespan vary according to season within and across species. Intrinsically, this variation should also determine changes in the spectral properties of foliar tissue. However, whether canopy phenology and leaf spectroscopy co-vary across species has seldom been tested in seasonal drylands.